2022
DOI: 10.3390/catal12020142
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Structural Properties and Optical Bandgap of PbO–Al2O3 Nanocomposites for Enhanced Photodegradation of Methylene Blue

Abstract: In the present work, PbO-x wt% Al2O3 nanocomposites (where x = 0, 10, 20, 30, 40, 50, 60, 70, and 100 wt%) were prepared by a microwave irradiation method. Their structural parameters, morphology, and chemical bonds, were investigated by X-ray diffraction (XRD), transmission electron microscopy (TEM), and Fourier-transform infrared spectroscopy (FTIR). It was noticed that the produced phases have an orthorhombic crystal structure and the smaller average crystallite sizes were formed when the ratio of Al2O3 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The PbO-modified TiO 2 introduced new electronic states above the valence band maximum of TiO 2 , which enhanced the photocatalytic activity of TiO 2 in the visible light region. Mebed et al [33] prepared PbO-Al 2 O 3 nanocomposites by microwave irradiation method and utilized it for methylene blue dye removal from wastewater under UV-visible or visible light irradiations. The combination of PbO and perovskite photocatalysts has also been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…The PbO-modified TiO 2 introduced new electronic states above the valence band maximum of TiO 2 , which enhanced the photocatalytic activity of TiO 2 in the visible light region. Mebed et al [33] prepared PbO-Al 2 O 3 nanocomposites by microwave irradiation method and utilized it for methylene blue dye removal from wastewater under UV-visible or visible light irradiations. The combination of PbO and perovskite photocatalysts has also been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…Sn doped showed the highest intensity which indicates weak interaction of Sn-O bond, hence capacity of carriers increases at trap center due the increase of emission intensity peaks [16]. However, Co doped showed weak intensity due to strong interaction between Co and O [28].…”
Section: Pl Emissions Analysismentioning
confidence: 95%
“…At the same time, electron localization takes place on the surface of TiO 2 , and hole localization takes place on PbO, modifying the photocatalytic activity of TiO 2 . Mebed et al [16] also reported the PbO-Al 2 O 3 nanocomposite synthesized by a microwave irradiation method and utilized for the degradation of methylene blue (MB) dye under UV-vis and visible light irradiation. MB dye is among the synthetic dyes widely used in textile industries which are physically and chemically stable compounds that affect aquatic life when released into the environment without treatment and effective management [7].…”
Section: Introductionmentioning
confidence: 99%
“…247 On the other hand, PbO 2 and PbO possess good chemical stability, optical transparency, and micro-hardness, which make them suitable for optoelectronic industry applications. 241,248,249 Lead oxide can also be found in the form including Pb 3 O 4 , PbO 2 , Pb 2 O 3 (α, β, and amorphous), and PbO (α, β). 250 PbO nanoparticles have a wide range of applications including energy storage devices, luminescence materials, gas sensors, modifiers in glass, lead crystals, pigments, nanoelectronic devices, lead glazes, UV blockers, pigments, and in decorative potteries.…”
Section: Metal Oxide Nanoparticlesmentioning
confidence: 99%
“…PbO has also been used in different metal oxide nanoparticles to modify their photocatalytic activity. Mebed et al 241 prepared PbO–Al 2 O 3 nanocomposite by the microwave irradiation method and utilized it for the removal of methylene blue from wastewater under UV-visible or visible light irradiations. Al 2 O 3 possesses a very wide bandgap of approximately 9 eV.…”
Section: Metal Oxide Nanoparticlesmentioning
confidence: 99%